Health services from the perspective of pregnant adolescents: an integrative review of the literature - Erica de Brito Pitilin; Carlos Alexandre Molena-Fernandes; Cláudio Claudino da Silva Filho (Universidade Federal de Santa Maria, 2015)
Aim: to identify on scientific literature the performance of health services in relation to teenage pregnancy from the perspective of the pregnant teenager. Method: the study is based on an integrative literature review by consulting three databases: Latin American Caribbean Literature on Health Sciences (LILACS), Specialized Bibliographic Data Base at Area Nursing Brazil (BDENF) and Medical Literature Analysis and Retrieval System Online (MEDLINE), by the descriptors "teenage pregnancy ", "perception" and "health services" in April 2014. Results: mostly, there was a technical assistance based on the physical needs of each pregnant teenager, followed by a discriminatory and judgmental assistance. Conclusion: it can be noticed that the assistance provided to the pregnant teenager presents a lack of a careful overview and a welcoming attitude that aims to listen, support and fulfill every need of this type of patient